Strategi Penerjemahan Film (Subtittling) dalam Serial Kartun Upin dan Ipin - Rachmawati, Raja (Jurnal Penerjemahan, 2016)
This article discusses the strategy utilized for the film subtitling in the cartoon series of Upin and Ipin. The objective of this article is to identify the words and sentences used in this carton series, and to analyze the strategies applied by the translator in the cartoon film subtitling text. This research uses the descriptive qualitative method and the purposive sampling technique. The film subtitling of Upin and Ipin serves as the source text for this research. The results show that several strategies are applied for the film subtitling in the Upin and Ipin cartoon series, they are the transfer, adaptation, cultural equivalence, descriptive equivalence, synonym, transposition, modulation, and paraphrase strategies. In addition, the research also finds that some words phrases and sentences in the subtitling of this cartoon series have unequivalent meaning. Keywords: strategy, subtitling, Upin and Ipin